Risk Factors for Sepsis after Retrograde Intrarenal Surgery: Single Center Experience - Jinseok Kang; Koo Han Yoo; Taesoo Choi; Gyeong Eun Min; Dong-Gi Lee; Hyung-Lae Lee; Jeonghyouk Choi (Urogenital Tract Infection)
Purpose To evaluate risk factors for sepsis after retrograde intrarenal surgery for treatment of renal stones. Materials and Methods We analyzed the clinical data of 243 patients with kidney stones who visited our institution between April 2017 and April 2023. Age, sex, body mass index, underlying disease, location and size of stones, previous history of stones, previous history of urinary tract infections, duration of surgery, preoperative drainage, application of ureteral balloon dilation, and laboratory test results were included in the analysis. Results The mean age of the patients was 58.4 (±15.0) years; there were more men (53.1%) than women (46.9%). Of the 243 patients, the overall rate of sepsis was 5.8% (n=14) and the total mortality rate was 0.4% (n=1). In univariate analysis, history of urinary tract infection (p=0.019), positive preoperative urine culture test (p=0.009), operative duration of more than 90 min (p=0.004), and application of ureter balloon dilation (p=0.016) were statistically significant. In multivariate analysis, positive finding in the urine culture test performed before surgery (p=0.003), operation duration >90 min (p=0.005), and use of balloon dilation during surgery (p=0.011) were statistically significant. Conclusions There is a risk of progression to postoperative sepsis if bacteria are detected in the urine culture before surgery, if the operative time exceeds 90 min, or if balloon dilation is performed during surgery. Given that the probability of progression to sepsis is approximately 6%, close observation and active treatment are needed for patients with these risk factors.